(untitled) (Journal of Atomic and Molecular Sciences, 2018)
Product Polarizations for the exchange reaction H'+HS and its isotopic variants on an accurate 1A' potential energy surface have been studied at collision energies of 10 kcal/mol by using the quasi-classical trajectory method (QCT). Product rotational angular momentum distributions P(θ_r) and P(φ_r) are calculated in the center-of-mass (CM) frame. Moreover, three generalized polarization-dependent differential cross sections (PDDCSs) are also computed. The results demonstrated that the isotopic effect displays sensitive effect on the product vector correlations. The reaction mechanism was discussed based on the properties of stereodynamics and the reactive trajectories.